Stochastic neural networks for feasibility checking - Strausz, György (Zielona Góra: Uniwersytet Zielonogórski)
Complex diagnosis problems, defined by high-level models, often lead to constraint-based discrete optimization tasks. A logical description of large, complex systems usually contains numerous variables. The first test of the logical description is typically to check the feasibility in order to know that there is no contradiction in the model.
Keywords: optimization; neutral networks; simulated annealing; mean-field approximation